Inhibitory efficacy, production dynamics, and characterization of postbiotics of lactic acid bacteria - Md. Moklesur Rahman; Awis Qurni Sazili; Siti Aqlima Ahmad; Khalilah Abdul Khalil; Mohammad Rashedi Ismail-Fitry; Md. Sazedul Karim Sarker (BMC Microbiology)
Abstract Antimicrobial resistance (AMR) poses a significant threat to human health and food safety. Lactic acid bacteria (LAB) produce bioactive compounds, known as postbiotics, that act as promising natural preservatives with broad-spectrum antimicrobial activity. This study aimed to evaluate the antimicrobial spectrum, production dynamics, and physicochemical properties of postbiotics derived from five LAB strains: Lactobacillus plantarum NBRC 3070, Lactobacillus acidophilus ATCC 4356, Lactobacillus casei ATCC 393, Lactobacillus rhamnosus GG ATCC 53103, and Bifidobacterium animalis subsp. lactis ATCC 27673. The antimicrobial activity of these postbiotics was assessed against several Gram-positive and Gram-negative pathogens. A crude bacteriocin-like inhibitory substance (BLIS), a postbiotic component, was partially purified using ammonium sulfate purification and characterized enzymatically. Its molecular weight was estimated by SDS-PAGE. The results showed that postbiotics, particularly those from L. plantarum and L. acidophilus, exhibited strong antimicrobial activity. The inhibitory effect was most pronounced against Escherichia coli, Salmonella Typhimurium, and Staphylococcus aureus after a 16-h exposure. The postbiotics production peaked between 24 and 36 h of incubation, achieving 85.71–89.28% inhibition. These postbiotics remained stable at high temperatures (up to 121 °C), across a wide pH range (3–5 and 9–11), and under varying salt concentrations. Neutralized cell-free supernatants from L. plantarum, L. acidophilus, L. casei, and L. rhamnosus GG retained antimicrobial activity, and enzyme treatments confirmed the proteinaceous nature of the BLIS. SDS-PAGE revealed diffuse protein bands between < 3.3 and 6.5 kDa. Lyophilization enhanced the concentration and stability of antibacterial compounds by reducing water content. In addition to BLIS, LAB strains produced other antimicrobial metabolites, including lactic acid, acetic acid, hydrogen peroxide, fatty acids, and notably, oleic acid. These postbiotic components remained effective after one month of storage at 4 °C and 20 °C for one month. The novelty of this study lies in its comprehensive characterization of postbiotics from well-established LAB strains across multiple functional parameters. Overall, the findings suggest that these LAB-derived postbiotics are stable, effective, and hold potential as natural antimicrobial agents in food preservation.